Glossary for the food industries - Gould, W. A. (Woodhead Publishing Ltd, 1995)
This totally revised and updated work is a definitive list of food abbreviations, terms, terminologies and acronyms compiled and edited by Wilbur A. Gould, Ph. D., who has drawn from his last 50 years of active work in the Food Industries to compile the most comprehensive list of food words published in book form.